Hsa_circ_0002062 Promotes the Proliferation of Pulmonary Artery Smooth Muscle Cells by Regulating the Hsa-miR-942-5p/CDK6 Signaling Pathway - Wang, Yali; Tan, Xiaoming; Wu, Yunjiang; Cao, Sipei; Lou, Yueyan; Zhang, Liyan; Hu, Feng (Frontiers in Genetics, 2021)
Abstract Currently, new strategies for the diagnosis and treatment of hypoxia-induced pulmonary hypertension (HPH) are urgently required. The unique features of circRNAs have unveiled a novel perspective for understanding the biological mechanisms underlying HPH and the possibility for innovative strategies for treatment of HPH. CircRNAs function as competing endogenous RNAs (CeRNA) to sequester miRNAs and regulate the expression of target genes. This study aimed to explore the roles of hsa_circ_0002062 on the biological behaviors of pulmonary artery smooth muscle cells (PASMCs) in hypoxic conditions. A number of in vitro assays, such as RNA-binding protein immunoprecipitation (RIP), RNA pull-down, and dual-luciferase assays were performed to evaluate the interrelationship between hsa_circ_0002062, hsa-miR-942-5P, and CDK6. The potential physiological functions of hsa_circ_0002062, hsa-miR-942-5P, and CDK6 in hypoxic PASMCs were investigated through expression modulation. Our experiments demonstrated that hsa_circ_0002062 functions as a ceRNA, acts as a sponge for hsa-miR-942-5P, and consequently activates CDK6, which further promotes pulmonary vascular remodeling. Therefore, we speculate that hsa_circ_0002062 could serve as a candidate diagnostic biomarker and potential therapeutic target for HPH.